The Influence Of Online Customer Reviews, Product Quality, And Promotions On Purchasing Decisions The Jisulife Handheld Fan On Tokopedia E-Commerce - Oktafiona; Winda Evyanto (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to analyze the influence of online customer reviews, product quality, and promotional strategies on purchasing decisions for the Jisulife Handheld Fan on the Tokopedia e-commerce platform. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through online questionnaires distributed to 120 Tokopedia users who have purchased Jisulife Handheld Fans. The findings show that online customer reviews, product quality, and promotions each have a positive and significant influence on purchasing decisions. Product quality is found to be the most dominant factor affecting consumer purchase intentions. The results of this research emphasize the importance of maintaining positive customer feedback, ensuring high-quality standards, and implementing attractive promotional strategies to strengthen consumer trust and stimulate buying behavior on e-commerce platforms. This study contributes to understanding the dynamics of online purchasing behavior and provides insights for marketers to optimize their digital strategies in competitive online marketplaces.